2008
DOI: 10.3390/molecules13061263
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitosan from Brine Shrimp (Artemia urmiana) Cyst Shells and Effects of Different Chemical Processing Sequences on the Physicochemical and Functional Properties of the Product

Abstract: Chitosan (CS) was prepared from Artemia urmiana cyst shells using the same chemical process as described for the other crustacean species, with minor adjustments in the treatment conditions. The influence of modifications of the CS production process on the physiochemical and functional properties of the CS obtained was examined. The study results indicate that Artemia urmiana cyst shells are a rich source of chitin as 29.3-34.5% of the shell’s dry weight consisted of this material. Compared to crab CS (select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 30 publications
4
46
1
2
Order By: Relevance
“…When the commercial chitosan was compared to the extracted chitosan, similarities were found in moisture (1.07-1.33%, respectively) and ash contents (0.59-0.61%, respectively) (p > 0.05). The results show similarities with the moisture and ash content of chitosan obtained from different sources (Artemia urmiana, snow crab processing) Tajik, Moradi, Rohani, Efrani, & Jalali, 2008).…”
Section: Resultssupporting
confidence: 59%
“…When the commercial chitosan was compared to the extracted chitosan, similarities were found in moisture (1.07-1.33%, respectively) and ash contents (0.59-0.61%, respectively) (p > 0.05). The results show similarities with the moisture and ash content of chitosan obtained from different sources (Artemia urmiana, snow crab processing) Tajik, Moradi, Rohani, Efrani, & Jalali, 2008).…”
Section: Resultssupporting
confidence: 59%
“…Degree of deacetylation (DD) value of chitosan is very important because it affects many physicochemical properties of chitosan including solubility, chemical reactivity, and biodegradability, and hence determines its appropriate applications [5,6]. No et al [7] stated that DD value must be at least 85% in order to achieve the desired solubility.…”
mentioning
confidence: 99%
“…However, bat guano had a slightly lower chitin content than cicada sloughs. Similarly, it was found that krill and Artemia cyst structures have high chitin contents, like the bat guano [28,29]. Nevertheless, bat guano will be a more prominent source compared with krill and Artemia cyst structures thanks to the natural stocks and easy collection.…”
Section: Resultsmentioning
confidence: 99%